Mental Illness in COVID‐19 Survivors - Moreira, Ana Filipa (2022)
Introduction: COVID‐19 disease has been declared a pandemic since March 2020. Studies carried out in previous pandemic contexts demonstrate a negative impact on mental health. In the context of SARS‐CoV‐2 infection, data suggests that the infection itself may be a predisposing factor for the onset or worsening of psychiatric disease. Material and Methods: We studied users of a Primary Care Unit in Northern Portugal diagnosed with SARS‐CoV‐2 infection between March and October 2020, with at least one month of follow‐up after cure, as well as a randomized sample of controls (1:1 ratio), in a total of 218 subjects. Results: We did not find significant differences in the onset or worsening of mental illness in the presence of SARS‐ ‐CoV‐2 infection. In this group, the number of days of isolation and the place of treatment were not associated with the onset or worsening of mental illness. In the total sample, the practice of physical exercise was associated with lower odds of onset or worsening of mental illness (p=0.039), and the presence of a history of mental illness was associated with higher odds of onset or worsening of it (p=0.001). Discussion: although COVID‐19 was not associated with onset or worsening of mental health, factors such as the practice of physical exercise and a history of mental illness were shown to have an impact on the onset or worsening of this variable in a pandemic context. Conclusion: SARS-coV-2 infection does not seem to be a determining factor in the worsening of mental health, there are other factors that may be more decisive.